Fashion Bukan Penanda Gender atau Usia Seseorang - I Gusti Agung Ayu Widyandari Kameswari; I Gusti Agung Malini (Jurnal Da Moda, 2023)
ABSTRACT Fashion is one industry that offers freedom in expressing one’s identity. But along with the times, there are many shifts in meaning so that stereotypes are formed on several types of fashion. Some of the things that have changed are stereotypes regarding the use of clothing colors according to gender and the use of clothing and accessories according to age. Fashion is flexible, non-rigid and non-binding which means that stereotypes are created because of hereditary understanding that is even done since infancy instilled by parents. This inaccurate understanding is a concern for fashion lovers to be creative because of the fear of being rejected by their environment. Therefore, research was conducted on fashion that refers to gender, norms and age of a person as an understanding and knoeledge for the community so that there is no missinterpretation of the meaning and nature of fashion. Keyword : Fashion, Gender, Norms, Age ABSTRAK Fashion merupakan salah satu industri yang menawarkan kebebasan dalam mengekspresikan jati diri seseorang. Namun seiring dengan perkembangan zaman, banyak terjadi pergeseran makna sehingga terbentuk stereotip pada beberapa jenis fashion. Beberapa hal yang berubah ialah stereotip mengenai penggunaan warna busana sesuai dengan gender serta penggunaan busana dan aksesoris sesuai dengan usia. Fashion bersifat fleksibel, tidak kaku dan tidak mengikat yang berarti stereotip tersebut tercipta karena pemahaman turun temurun yang bahkan dilakukan sejak bayi yang ditanamkan oleh orang tua. Pemahaman yang kurang tepat tersebut menjadi kekhawatiran bagi para pecinta fashion untuk berkreasi karena adanya ketakutan jika mendapat penolakan dari lingkungannya. Oleh karena itu dilakukan penelitian terhadap fashion yang merujuk kepada gender, norma dan usia seseorang sebagai pemahaman dan ilmu bagi masyarakat agar tidak terjadi salah pengartian makna dan sifat fashion. Kata Kunci : Fashion, Gender, Norma, Usia